# The equation of t

Given that the curve y = x2 – 3x + 2

The tangent passes through point (x, 0)

0 = x2 – 3x + 2

(x-2)(x-1)=0

x = 1 or 2

Equation of the tangent:

(y-y1)=Slope of tangent×(x-x1)

Case: 1

When x = 2

Slope of tangent = 1

Equation of tangent:

y = 1× (x – 2)

x – y – 2 = 0

Case: 2

When x = 1

Slope of tangent = -1

Equation of tangent:

y = -1× (x – 1)

x + y – 1 = 0

Hence, option B is correct.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses
RELATED QUESTIONS :

Find the equationRD Sharma - Volume 1

Find the equationMathematics - Board Papers

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the equationRD Sharma - Volume 1

Find the conditioMathematics - Exemplar